„Hiszem és remélem, hogy...hamarosan visszatérhet a régi barátság és megértés" : Horthy Miklós mohácsi beszéde és a szerb orientáció alternatívája a magyar külpolitikában - Vizi, László Tamás (Közép-Európai Közlemények, 2013)
At the end of august 1926., whole Hungary was burning in ceremonial fever. The nation prepared for the ceremony of the four hundredth anniversary of the battle of Mohács. Just before the anniversary they made several events in Mohács, and country-wide. The central celebration was on the 29th august 1926. Contemporary newspapers reported the events in details: about the foundationstone of the Votive Church of Mohács, about the wreathing of the battlefield and King Louis II.’s tomb. This essay’s first part recalls these festive events. It quotes the most important speeches. Especially highlighted the speech of the Republic of Turkey’s Embassy and Miklós Horthy, Hungary’s governor’s wreathing speech. The second part of the article presents and analysis the speech’s domestic and international political reacts. Tries to answer the question that was Horthy’s speech the announcement of the Hungarian foreign policy’s Serbian orientation? In order to strike a gap on the Little Entente’s ring. Or conversely. A non-coordinated governor’s action, that did not brought forward the merits of the Hungarian–Yugoslav rapprochement. But on the contrary. It prevented an agreement between Hugary and Yugoslavia. Interestingly, finally the speech had forign policy results: Opened up the possibility of cooperation and approchement between Budapest and Rome.